Pengaruh Frekuensi Perdagangan, Rasio Keuangan, dan Kapitalisasi Pasar Terhadap Return Saham Syariah pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2016-2019 - Ruswandi, Muhamad Safitri; Zakaria, Adam; Noviarini, Diena (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of trading frequency, financial ratios, and market capitalization on sharia stock returns. The independent variables used in this study are stock trading frequency, earnings per share, return on equity, debt to equity ratio, and market capitalization. The dependent variable used in this study is stock returns. This study uses secondary data, namely financial statements and annual reports of companies listed in the Jakarta Islamic Index (JII) index on the Indonesia Stock Exchange for the 2016-2019 period (100 observations). The sampling method used in this research is the purposive sampling method. This study uses the panel data analysis method which is processed using the EViews 12 application. The results show that trading frequency does not affect on sharia stock returns. Earning per share does not affect on sharia stock returns. Return on equity does not affect on sharia stock returns. The debt to equity ratio does not affect on sharia stock returns. Market capitalization has a positive effect on sharia stock returns